Financial Distress Analysis of Primary Consumer Goods Manufacturing Companies in Indonesia Stock Exchange - Niken Nabilla Putri Lubis; Yul Tito Permadhy (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research is using quantitative study aimed to determine and analyze the influence of liquidity, leverage, profitability and operating capacity on financial distress. The sample in this study uses the primary consumer goods sector companies on the Indonesia Stock Exchange as many as 67 companies in 2018-2020. This study uses purposive sampling as a sampling technique. The analysis technique in this study was used Microsoft Excel 2016 with the statistical tool E-Views 12.0. The results of this study indicate that (1) liquidity has a negative effect on financial distress (2) leverage has a positive effect on financial distress (3) profitability doesn’t have effect on financial distress (4) operating capacity has a negative effect on financial distress.